1986
DOI: 10.1016/0014-5793(86)80040-0
|View full text |Cite
|
Sign up to set email alerts
|

The rate‐limiting step and nonhyperbolic kinetics in the oxidation of ferrocytochrome c catalyzed by cytochrome c oxidase

Abstract: The level of reduction of cytochrome a and cua during the oxidation of ferrocytochrome c has been determined in stopped‐flow experiments. Both components are partially reduced but become progressively more oxidized as the reaction proceeds. When all cytochrome c has been oxidized, cua is also completely oxidized, whereas cytochrome a is still partially reduced. These results can be simulated on the basis of a model which requires that the intramolecular electron transfer from cytochrome a and cua to cytochrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 22 publications
(2 reference statements)
1
14
0
Order By: Relevance
“…Furthermore, the models ignore the requirement that a pump protein must exist in two different conformational states with different substrate affinities, as also observed experimentally. The models based on a nonproductive binding site (13,16) must assume that product dissociation is strictly rate limiting, but this is excluded by the observation that cytochrome a is always partially reduced in the steady state (14). (25, *).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the models ignore the requirement that a pump protein must exist in two different conformational states with different substrate affinities, as also observed experimentally. The models based on a nonproductive binding site (13,16) must assume that product dissociation is strictly rate limiting, but this is excluded by the observation that cytochrome a is always partially reduced in the steady state (14). (25, *).…”
Section: Discussionmentioning
confidence: 99%
“…Instead the existence of two active sites has generally been assumed (9,12), and an electrostatic model involving a single catalytic site and a second, nonproductive, binding site has also been proposed (13). In a recent paper (14) we have provided experimental evidence against the latter model and furthermore suggested that the nonhyper- bolic kinetics of cytochrome oxidase is a direct consequence of its function as a proton pump. It is not, however, sufficient to demonstrate this obligatory relation between proton pumping and substrate kinetics.…”
mentioning
confidence: 94%
“…The chrome a3-CuB site does not occur in the singly reduced oxidashed line represents a forbidden transition. For further explanadase [15,16]. tions, see the text.…”
Section: E (Red)mentioning
confidence: 99%
“…If only one catalytic site is considered [l 11, a control site and/or a reaction scheme similar to that proposed for cytochrome oxidase [12] would be required in order to explain the concave nature of the Eadie Hofstee plot.…”
Section: Proton Translocation Is Coupled Not Only To the Tri-site Cyclementioning
confidence: 99%